AN UNSTEADY MAGNETO HYDRO DYNAMIC HEAT TRANSFER FLOW THROUGH A POROUS MEDIUM WITH RADIATION EFFECT. - DHARMAIAH G (Innovare Journal of Engineering and Technology, 2017)
Abstract: The joined impact of a transverse attractive field and radiative heat exchange on unsteady stream of a directing optically thin visco-elastic fluid through a pivoting channel loaded with immersed permeable medium and non-uniform dividers temperature has been talked about. It is accepted that the liquid has little electrical conductivity and the electromagnetic power delivered is little. The explanatory arrangements are gotten for the issue making utilization of perturbation technique. The impacts of the radiation and the magnetic field parameters on velocity profile for various estimations of the visco-elastic parameter with the blend of the other stream parameters are delineated graphically, and physical parts of the issue are talked about. Keywords: Radiation effects, heat transfer, MHD flows, porous medium.